Evangelio, política y memoria en los Toba (qom) del Chaco argentino - César Ceriani Cernadas (Centre de Recherches sur les Mondes Américains, 2011)
This article deals with historical predicaments regarding identity and politics in the case of the Toba (Qom) appropriation of Pentecostal Christianity. Holding the native name of Evangelio, this religious movement obtained institutional strength during the sixties and, in subsequent decades, was a dynamic as well as conflictive expression. Since its origins, leaders and members as well showed ambivalents relation between ethnic reaffirmation, spiritual performance, and political agency. In this way, this work explores the disputes about meanings that people built in relation to memory, ethnic adscription, generational cleavage and religious celebrations. Taking as starting point a particular historical and sociological locus of the so-called aboriginal Evangelic field of the Chaco region, the article analyzes the cultural forms of the Toba Evangelic experience by observing problems of symbolic and generational kind in order to connect them with the collective memory and ethnic self-perception. Finally, this study approaches the impact of the Evangelical movement and the national sociopolitical context over the configuration of leadership along with its concomitant tensions.